ER Disposal Pathways in Chronic Liver Disease: Protective, Pathogenic, and Potential Therapeutic Targets - Duwaerts, Caroline C.; Maiers, Jessica L. (Frontiers in Molecular Biosciences, 2022)
The endoplasmic reticulum is a central player in liver pathophysiology. Chronic injury to the ER through increased lipid content, alcohol metabolism, or accumulation of misfolded proteins causes ER stress, dysregulated hepatocyte function, inflammation, and worsened disease pathogenesis. A key adaptation of the ER to resolve stress is the removal of excess or misfolded proteins. Degradation of intra-luminal or ER membrane proteins occurs through distinct mechanisms that include ER-associated Degradation (ERAD) and ER-to-lysosome-associated degradation (ERLAD), which includes macro-ER-phagy, micro-ER-phagy, and Atg8/LC-3-dependent vesicular delivery. All three of these processes are critical for removing misfolded or unfolded protein aggregates, and re-establishing ER homeostasis following expansion/stress, which is critical for liver function and adaptation to injury. Despite playing a key role in resolving ER stress, the contribution of these degradative processes to liver physiology and pathophysiology is understudied. Analysis of publicly available datasets from diseased livers revealed that numerous genes involved in ER-related degradative pathways are dysregulated; however, their roles and regulation in disease progression are not well defined. Here we discuss the dynamic regulation of ER-related protein disposal pathways in chronic liver disease and cell-type specific roles, as well as potentially targetable mechanisms for treatment of chronic liver disease.